International Pediatric Otolaryngology Group (IPOG) survey: Efforts to avoid complications in home tracheostomy care. (February 2021) - Caloway, Christen; Balakrishnan, Karthik; Boudewyns, An; Chan, Kenny H.; Cheng, Alan; Daniel, Sam J.; Fayoux, Pierre; Garabedian, Noel; Hart, Catherine; Moreddu, Eric; Muntz, Harlan; Nicollas, Richard; et al.
Abstract: Objective: To provide guidance for home care tracheostomy management in the pediatric population. The mission of the IPOG is to develop expertise-based recommendations for the management of pediatric otolaryngologic disorders with the goal of improving patient care. Methods: Survey of expert opinion by the members of the International Pediatric Otolaryngology Group (IPOG). Results: Survey results provide guidance for caregiver teaching, the reuse of tracheostomies and suction catheters while inpatient and following discharge, acceptable sterilization practices for tracheostomies, tracheitis workup and management, and outpatient follow-up practices. Conclusion: This presentation of common home tracheostomy care practices are aimed at improving patient-centered care in the pediatric population.